China's economic integration with the Greater Mekong Sub-region: An empirical analysis by a panel dynamic gravity model - Saleh Shahriar; Lu Qian; Sokvibol Kea (Kiel Institute for the World Economy (IfW), 2018)
The purpose of this study is to fill an existing gap in the literature by addressing the following research question: what are the major determinants of China's regional economic integration with the Greater Mekong Sub-regional countries (GMS), namely; Cambodia, Laos, Myanmar, Thailand and Vietnam? The author measures the economic integration in terms of bilateral trade and foreign direct investment (FDI). In accordance with the literature, the present study adopts a panel gravity framework method to analyze the significant factors affecting the bilateral aggregate exports flows of China with five economies of the Greater Mekong sub-region. Data were collected from both the Chinese national and the international sources over the period of 23 years, spanning from 1993 to 2016. The time period was chosen on the consideration of data availability. The result shows that the gravity model is econometrically fitted to our dataset. Among other factors GDP, bilateral exchange rate, and population have a positive impact on regional trade integration with the GMS. The author's second-stage regression analysis confirms that China's accession to the WTO impacts positively on the bilateral trade. China's accession to the WTO is a significant factor for facilitation of trade flows. As expected, distance hinders regional trade. Furthermore, the role of historical trade relationship between China and GMS countries is estimated in the dynamic model. The result shows that China's trade relationship with GMS countries is determined historically.
https://doi.org/10.7910/DVN/V9VEBM
Keywords: F14; F15; 330; China; regional economic integration; dynamic gravity model; Greater Mekong Sub region (GMS); exports; panel data